APLIKASI SISTEM INFORMASI AKUNTANSI PERSEDIAAN SPARE PART SEPEDA MOTOR - Muhtarudin Muhtarudin (LPKIA, 2023)
The main topic of discussion in this minor thesis is focused on the spare part inventory accounting information system that is implemented in the warehouse section of PT Sejahtera Inti Anugrah Perkasa which carries out various forms of activities related to Spare Part Inventory. After analyzing and studying the activities that occur, such as when buying Stock Inventory which is carried out by the warehouse department itself so that when making evidence or documents it is less effective and prone to fraud, because of that there are often delays in presenting reports related to spare part inventory.With the above problems, a Spare Part Inventory Accounting Information System Application will be built which has facilities that can support the presentation of reports needed by the company concerned with spare part inventory.This Spare Part Inventory Accounting Information System application was built using Microsoft Access 2013. The information system development methodology used is a prototype starting with listening to consumers, building and repairing prototypes and testing them. The tools used are. Flowmap, Contest Diagram, DFD (Data Flow Diagram), Data Dictionary and ERD (Entity Relationship Diagram)